PENGARUH CELESTIAL INCENTIVES DAN ECONOMIC INCENTIVES TERHADAP MOTIVASI DAN DAMPAKNYA PADA KUALITAS JASA DAN KELUHAN PELANGGAN (Studi Kasus Kartu SHAR-E Bank Muamalat Indonesia) - Milwani . (Prodi Manajemen Fakultas Ekonomi Universitas Pamulang, 2013)
The result of this research show that the celestial incentives positively associated with motivation, the economic incentives positively associated with motivation, the economic incentives positively associated with service quality, motivation positively associated with service quality and service quality positively associated with customer complain. Contrary, the celestial incentives negatively associated with service quality, the celestial incentives negatively associated with customer complain and the economic incentives negatively associated with customer complain. This result of this research show that economic incentives factors still dominated in sharia bank. This result indicates that customer will satisfy or complain associated of service quality factors. This service quality factors associated of motivation, and motivation factors associated with incentive. Keywords : celestial incentives, economic incentives., motivation, service quality and customer complain.